Collaborative approaches to wellness and health equity in the Circumpolar North: Introduction to the Special Issue. Issue 2 (28th January 2019) - Pollock, Nathaniel; Cunsolo, Ashlee
ABSTRACT: This special issue brings together a series of papers that were presented at the Northern, Rural, and Remote Health Conference in Labrador, Canada. In this collection, scholars and community leaders use local examples to explore some of the most pressing issues in Circumpolar health: Indigenous self-determination in health care and health research; access to traditional medicines; language and identity; youth engagement; mental health; climate change; and health technology. Recognizing the dynamic ways that these topics were raised at the conference, we've included a diverse slate of papers: from commentary essays and case studies, to primary research and evidence synthesis. The goal of this special issue is to bridge local insights, innovations, and varied forms of evidence from the Circumpolar North, with global conversations about health equity, health system transformation, and the rights of Indigenous peoples. This editorial provides an overview of the conference and an introduction to the scholarship that emerged from it.